Existence, uniqueness and stability of traveling wavefronts for nonlocal dispersal equations with convolution type bistable nonlinearity - Guo-Bao Zhang; Ruyun Ma (Electronic Journal of Differential Equations, 2015)
This article concerns the bistable traveling wavefronts of a nonlocal dispersal equation with convolution type bistable nonlinearity. Applying a homotopy method, we establish the existence of traveling wavefronts. If the wave speed does not vanish, i.e. $c≠ 0$, then the uniqueness (up to translation) and the globally asymptotical stability of traveling wavefronts are proved by the comparison principle and squeezing technique.